Crisis responses, opportunity, and public authority during Covid‐19's first wave in Uganda, the Democratic Republic of Congo, and South Sudan. (29th November 2021) - Kirk, Tom; Green, Duncan; Allen, Tim; Carayannis, Tatiana; Bazonzi, José; Ndala, José; Stys, Patrycja; Muzuri, Papy; Nyenyezi, Aymar; Vlassenroot, Koen; Nyuon, Abraham Diing Akoi; Macdonald, Anna; et al.
Abstract : Discussions on African responses to Covid‐19 have focused on the state and its international backers. Far less is known about a wider range of public authorities, including chiefs, humanitarians, criminal gangs, and armed groups. This paper investigates how the pandemic provided opportunities for claims to and contests over power in Uganda, the Democratic Republic of the Congo, and South Sudan. Ethnographic research is used to contend that local forms of public authority can be akin to miniature sovereigns, able to interpret dictates, policies, and advice as required. Alongside coping with existing complex protracted emergencies, many try to advance their own agendas and secure benefits. Those they seek to govern, though, do not passively accept the new normal, instead often challenging those in positions of influence. This paper assesses which of these actions and reactions will have lasting effects on local notions of statehood and argues for a public authorities lens in times of crisis.